Positive effects of hearing and speech rehabilitation on lexical range quality in hearing impaired children - Maletic Sekulic, Ivana; Veselinović, Ivana; Jeličić, Ljiljana; Šijan-Gobeljić, Mirjana; Dragutinović, Ninoslava (Vojnosanitetski pregled, 2020)
Background/Aim. Initial experiences in rehabilitation of children with cochlear implants and frequent debates regarding the effects of their application have imposed the necessity to compare the effects of speech rehabilitation  in children with hearing aids with those having cochlear implants. The aim of this study was to evaluate and compare the level of lexical development in hearing impaired children who are involved in the process of hearing and speech-language rehabilitation and who were amplified by hearing aids or cochlear implants. Methods. The sample consisted of 55 children aged 3–6 years, diagnosed with prelingual bilateral hearing impairment with a hearing threshold above 90 dB. All examined children had average intellectual abilities and no additonal impairments. The sample was divided into 2 groups: E1 group consisted of 30 children with cochlear implants and E2 group consisted of 25 children who were amplified by individual hearing aids. Research methodology included a Test of Vocabulary. The testing was performed individually. A year after the testing, a retest was done. Statistical analysis was performed using the SPSS v. 17 for Windows. Results. The largest number of children had average achievements on a Test of Vocabulary during initial testing. After a year (retest) significant improvements were noticed. A large number of children had above average achievements (46.7% in the E1 and 36% in the E2 group) while the number of children with below average achievements was significantly reduced (3.3% in the E1 and 8% in the E2).  A comparative analysis of the test and those with gearing aids achievements showed that there was no statistically significant difference between children with cochlear implants and retest. Conclusion. Significant improvement of the achievements on retest in both groups can be explained by positive effects of systematic, planned, intensive and continuous rehabilitation of hearing impaired children, and not by application of certain type of hearing amplification.
Keywords: hearing disorders; child, preschool; hearing aids; cochlear implants; speech; rehabilitation; vocabulary; surveys and questionnaires